Composition and Characteristics of Safflower Seed and Oil - AHMED, AHMED A.; MOHAMED, MOSTAFA A.; RANA, MUHAMMAD S. (The Libyan Journal of Agriculture, 2023)
Safflower (Carthamus tinctorius} seeds were brought from the Agriculture Experimental Station at Geran (S.P.L.AJ.). Composition of seeds along with physical and chemical properties of oil is reported. Neutral fats were separated by silicic acid column and thin layer chromatography. The methyl esters were quantitated by GLC analysis. The seeds contain 5.036% moisture: their chemical composition on a dry basis is: crude fat 31.58%; crude protein 17.44%; crude fibre 24.28%; ash. 3.65% and total nitrogen 3.06%. The characteristics of the seed oil are: specific gravity at 25 C. 0.9322; refractive index at 25 C. 1.4713; saponification value. 199.22; iodine value. 143.56; Reichert Meissl value. 0.57; Polenske value. 3.76; free fatty acids, 0.16: TBA number, 0.31; acid value. 0.32; and viscosity 69.322 (Cp. at 20 C). The distribution of principal fatty acids in neutral fat is: linoleic, 57.2%; oleic. 23.3%; Palmitic. 12.1%; stearic. 4.8%; and arachidic. 1%. The linolenic acid is in traces.